Linking minds and growth: maternal mental health and child stunting : A systematic review - Pratiwi, Mayditania Intan Bunga; Qirani, Ida Ayu Devi; Anugrah, Pani Matin; Ocviyanti, Dwiana; Irwinda, Rima (World Nutrition Journal, 2024)
Maternal mental health during pregnancy has a significant impact on early childhood development, but its association with child growth outcomes, notably stunting, has received less attention, particularly in Indonesia.